Vpliv plevelov na rast, razvoj in kakovost hmelja - Simončič, Andrej (2019)
The Influence of Weeds on the Growth, Development and Quality of Hops. Five-year research has been carried out at the Slovenian Institute for Hop Research and Brewing in Žalec to study the influence of weeds on hop growth and the quantity and quality of yield. In field trials the influence of different weed species, their number and weediness duration on the quantity and quality of yield, including hop growth was studied. It was established that annual weeds regardless of their number and weediness duration did not statistically significantly affect the yield quantity and quality in the first two years, while the negative effect of Chenopodium album and Amaranthus retroflexus increased after a few years. Weediness caused by perennial weeds, such as Symphytum officinale, Rumex obtusifolius and Convolvulus arvensis impaired hop growth already in the second year of research resulting in smaller and lower yield quality. While studying the influence of various types of irrigation on weed and hop development and their consequential effect on the hop yield in the three-year field trials, it was found that the development of weeds could be influenced by different types of irrigation. Despite the differences in the weed mass, the influence of different irrigation systems on the hop yield was not statistically significant.
Keywords: hops; weeds; hops-weeds interaction; weed control; hops irrigation and weed; hop yield; hop quality